Understanding PCR Policy in Indonesia: Between Healthy and Business Issues: Health and Political Literacy Study - Ade Iskandar; Budi Sulistiyo Nugroho; Sri Sugiarti; Diansanto Prayoga; Dyanasari Dyanasari (Budapest International Research and Critics University, 2022)
Since the world's covid outbreak, each country has issued a response policy, including prevention and treatment. One of the preventions carried out by Indonesian youth is to carry out special tests with much attached policies and tell the stories of various parties. The authors believe that today's television is full of practices between health conflicts and conflicts of interest of the parties. To prove these assumptions and allegations, we conducted an instant data search on the application of health journals and also social crises in Indonesia, and we found that the data was then taken by a phenomenological approach and then analyzed with data coding, in-depth analysis, rigorous evaluation and also concluding passing through the data. Various high interpretations to obtain valid and accurate data in answering the problems of this study. Based on the available data, then the discussion we found that the understanding of the physical test, which is a government policy has found that the issue of pollution is a problem where we found several interests and conflicts that occurred so that until now it remains an unsolved problem. Hopefully, this data will be valuable input for efforts to improve and provide the first service to understand the meaning of the PCR test in Indonesia.